The Political Role of the Survey Agency in Indonesia Democracy - Ma'mun Murod; Lusi Andriyani; Djoni Gunanto; Usni; Norsiah Abdul Hamid (Journal of Local Government Issues (LOGOS), 2022)
This article has main points of discussion on issues related to how political survey institutions should operate to support democracy in Indonesia. The purpose of the study in this article is to map the ideal operational pattern of political survey institutions to support democracy in Indonesia. By using the literature study method, this article collects various literature sources to draw conclusions from these problems. This article has found that there are various ethical violations in political surveys that have been carried out for some time.  The problem relates to the unholy alliance with political consultants, contemporary business models, manipulation and misleading survey results, and survey method techniques. The recommendation from this article is that political pollsters should prioritize integrity, transparency, and accountability over profit. This will certainly be positively correlated with developing democracy in Indonesia.